Before the coffee gets cold - Kawaguchi, Toshikazu, 1971- (Picador, an imprint of Pan Macmillan, 2019)
"In a small back alley in Tokyo, there is a café which has been serving carefully brewed coffee for more than one hundred years. But this coffee shop offers its customers a unique experience: the chance to travel back in time. In Before the Coffee Gets Cold, we meet four visitors, each of whom is hoping to make use of the café's time-travelling offer, in order to confront the lover who left them, receive a letter from their husband whose memory has begun to fade, see their sister one last time, and meet the daughter they never got the chance to know. But the journey into the past does not come without risks: customers must sit in a particular seat, they cannot leave the café, and finally, they must return to the present before the coffee gets cold... Toshikazu Kawaguchi's beautiful, moving story explores the age-old question: what would you change if you could travel back in time? More importantly, who would you want to meet, maybe for one last time?" --